Adolescence: A dilemma of social protection policy in Angola - Issenguele , Isaías Francisco Gaspar; Pimentel, Rosalinda Chedian (Seven Editora, 2024)
This text emerges from the need to contribute to the promotion of moments of reflection on social protection in Angola on the social protection of "adolescents". Angola is a country that is part of the 54 countries on the African continent. It has an estimated population of 30,000,000 inhabitants. And, of this total, 47% are under 18 years of age and mostly from poor families, living in underdeveloped or peripheral areas, with little supply, or even without schools, hospitals, basic sanitation, and sports infrastructure, and relegated to the world of delinquency, prostitution, drug use and other problems. The article aims to reinforce and instigate the debate on the social protection of adolescents from the perspective of the social critical approach, making use of the theoretical perspective that is not satisfied with the mere appearance of social facts or refractions of the social question. This reflection was guided by the principles of the Marxist historical-critical and dialectical method. The reflection on the theme was made through three points: the first deals with Adolescence - Historical foundations; and, the second, Adolescence in Angola: challenges and possibility, and the third and last, Social Protection for adolescents in situations of social unprotection in Angola. Itwas concluded that, as in every part of the world, in Angola, due to the level of precariousness of the population in general and of adolescents, the creation and implementation of social protection policies is of extreme urgency and emergency. DOI:https://doi.org/10.56238/sevened2024.007-005